EXPLORATION OF SERVICE DELIVERY CHALLENGES IN SOUTH AFRICA - Shikha Vyas-Doorgapersad (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Several issues affect South Africa, including poverty, unemployment, food insecurity, crime, floods, and climate change. These difficulties have led to civil unrest, mass frustration, as well as community protests. The government is generally expected to provide better services in the areas of suitable housing, energy supply, water and sanitation provisions, improved employment and educational opportunities, suitable infrastructure, and workable health facilities. Aside from all these difficulties, South Africa is also dealing with an electricity crisis that is impacting people's daily lives through frequent, advanced, or interval-based load-shedding. The water system needs urgent repair. There are constant leaks from the rusty, old water pipes. Some provincial suburbs go without water or electricity for a few hours or days at a time. There are many items on the list. The article attempts to gather data to support the cause of subpar service performance. There are numerous demands for service delivery, but there aren't enough resources to fulfill them. Insufficient financial, human, technical, and technological resources make it difficult for the government to provide all the facilities that are requested. Protests about service delivery result from unfulfilled demands. To provide seamless services without regard to time or location constraints, the study intends to investigate the challenges facing the traditional mode of service delivery. This transformation will be achieved through the adoption of technological interventions. Additionally, the study investigates a few potential roadblocks to the service delivery procedures. Information for the qualitative study is gathered through documents and literature reviews. Conceptual and document analysis are used to analyse the gathered data. According to the study, by using appropriate digitalised coordination and a sufficient infrastructure based on information technology, interventions related to the fourth industrial revolution (4IR) may be able to completely change the way services are delivered.